Breast Cancer Vaccines: New Insights - Benedetti, Rosaria; Dell’Aversana, Carmela; Giorgio, Cristina; Astorri, Roberta; Altucci, Lucia (Frontiers in Endocrinology, 2017)
Breast cancer (BC) is a persistent global challenge for its high frequency in women (although it seldom occurs in men), due to the large diffusion of risk factors and gene mutations, and for its peculiar biology and microenvironment. To date, BC can benefit from different therapeutic strategies involving surgery, ablation, chemotherapy (CT), radiotherapy (RT) and more specific approaches such hormone therapy (HT) and the administration of various substances impairing cancer growth, aggressivity and recurrence with different modalities. Despite these relatively wide chances, also used in combinatory protocols, relevant mortality and relapse rates, often associated with resistant phenotypes, stress the need for a personalized-medicine based on prompting the patient’s immune system (IS) against cancer cells. BC immunogenicity was latterly proven, so the whole immunotherapy field for BC is still at a very early stage. This immunotherapeutic approach exploits both the high specificity of adaptive immune response and the immunological memory. This review is focused on some of the majorly relevant BC vaccines available (NeuVax, AVX901 and INO-1400), providing a description of the more promising clinical trials. The efficacy of cancer vaccines highly depends on the patient’s immune system and a wide optimization is needed in terms of targets’ selection, drug design and combinations, dose-finding, protocol structuring and patients’ recruitment; moreover, new standards are being discussed for the outcome evaluation. However, early-phases excellent results suggest that the manipulation of the IS via specific vaccines is a highly attractive approach for BC.